Image manipulation for radiography focus on mAs values / Nor Syuhada Salehudin - Salehudin, Nor Syuhada (2007)
Medical imaging is one of the difficult subjects to teach. Currently, the lectures have faced the difficulty to explain and to give a good example to their student about the x-ray image in the classroom. If this problem is continuously happen, it would let the misunderstanding among the student on how to gain the better explanation about the subject. To overcome this difficulty, a prototype is developed to help the lecture to give a proper learning to their student. This prototype has been implemented with the multimedia concept and integrated with the Java programming language. Several image sampling has been tested using this prototype to ensure that it can work on it task. Some adjustment will be making to get the best setting. Finally, the result which is the image with the brightness changes is displayed on the interface.